2011
DOI: 10.1093/molbev/msr189
|View full text |Cite
|
Sign up to set email alerts
|

Convergent Evolution of Endometrial Prolactin Expression in Primates, Mice, and Elephants Through the Independent Recruitment of Transposable Elements

Abstract: Prolactin (PRL) is a multifunctional signaling molecule best known for its role in regulating lactation in mammals. Systemic PRL is produced by the anterior pituitary, but extrapituitary PRL has also been detected in many tissues including the human endometrium. Prolactin is essential for pregnancy in rodents and one of the most dramatically induced genes in the endometrium during human pregnancy. The promoter for human endometrial Prl is located about 5.8 kb upstream of the pituitary promoter and is derived f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
66
0
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 92 publications
(67 citation statements)
references
References 34 publications
(43 reference statements)
0
66
0
1
Order By: Relevance
“…An arrow indicates that a region has promoter activity; size of arrow indicates strength of promoter. Note that strength of mouse promoter has not been tested but location has been determined; rabbits do not express decidual prolactin, so their MER20/ MER39 region is assumed here to lack a promoter (5). Also note that the presence of decidual prolactin transcripts has not been tested in lemurs.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…An arrow indicates that a region has promoter activity; size of arrow indicates strength of promoter. Note that strength of mouse promoter has not been tested but location has been determined; rabbits do not express decidual prolactin, so their MER20/ MER39 region is assumed here to lack a promoter (5). Also note that the presence of decidual prolactin transcripts has not been tested in lemurs.…”
Section: Methodsmentioning
confidence: 99%
“…In a recent paper we showed that the prolactin gene was independently recruited into uterine expression in primates, mice, and elephants by the co-option of different transposable elements, highlighting the frequency at which TEs can be recruited and their importance in gene regulatory innovation (5). Here we trace the evolutionary history and function of transposable elements in one of these groups-the primates-to understand precisely how uterine prolactin expression evolved via these elements, and why.…”
mentioning
confidence: 86%
“…Prolactin (Prl) for example, a gene involved in regulating lactation in placental mammals, has many alternative transcripts [33]. Placental mammals such as dogs and armadillos show no evidence of a myometrial Prl transcript, while humans, some New World monkeys, mice and elephants all express Prl transcripts; however, each species expresses different splice variants with alternative transcription start sites [34]. Another gene that has multiple alternative transcripts across the placental mammals is the gene encoding aromatase (CYP19).…”
Section: Comparative Placental Transcriptomicsmentioning
confidence: 99%
“…Consider the expression of prolactin (PRL) in the endometrium of elephants, rodents, and primates but not in the endometrium of rabbits, pigs, dogs, armadillos, or opossums (Emera et al 2012). Three independent origins of endometrial PRL expression are associated with insertions from four families of transposable elements (TEs) that occurred at different times during mammalian evolution (Lynch et al 2008;Emera et al 2012).…”
mentioning
confidence: 99%
“…Three independent origins of endometrial PRL expression are associated with insertions from four families of transposable elements (TEs) that occurred at different times during mammalian evolution (Lynch et al 2008;Emera et al 2012). Some insertions were not associated with endometrial expression for many millions of years (Emera and Wagner 2012a).…”
mentioning
confidence: 99%